Strategi Pemerintah Desa Dalam Pengembangan Bumdesa Madaparama Jaya Di Kabupaten Dompu - Wawan Erdian Wansyah; Adji Suradji Muhammad (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The strategy process for developing Village-Owned Enterprises (BUMDesa) is an important step to advance and develop village economic potential. As stated in the function of BUMDesa according to Law Number 06 of 2014 concerning Villages, it is as a driver of the village economy, as a business institution that generates original village income (PADesa) and as a means to encourage accelerated improvement in village welfare. With the presence of BUMDesa, it is hoped that the Village will become more independent and able to improve the community's economy and be able to contribute to increasing Village income and meeting the Village's basic needs. The Village Government's strategy in developing BUMDesa Madaparama Jaya, the Village Government must identify and analyze the various approaches taken by the village government to advance BUMDesa Madaparama. in accordance with the objective conditions of the existing environment in implementing the strategy to develop BUMDesa Madaparama, but in fact the lack of competent human resources and community involvement is an obstacle in implementing the village government's strategy for developing BUMDesa Madaparama. The research method used in this research is descriptive qualitative with data collection through observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and conclusions. The results of this research are that researchers found that the village government's strategy in developing BUMDesa has been carried out well, even though there are still shortcomings and obstacles such as lack of human resource competency, minimal budget funds provided and low community participation in supporting the Village Government's strategy in Madaparama BUMDesa development will be even better in the future.